(untitled) (Bangladesh Journal of Urology, 2020)
A 25 year male patient presented with the complaints of passage of urine through two openings on his penis, with deformities of penis since birth. After birth his parents noticed, when he micturates, urine comes through an opening on the proximal part of dorsal surface of penis in addition to the opening on the tip of glans penis. The penis is also a bit deformed and dorsal part of corona glandis is bifid. No treatment for the anomaly was taken. At puberty his testes, scrotum and other secondary sexual characteristics developed normally. He feels sexual attractions to opposite sex and experiences nocturnal emissions periodically. His penis erects on sexual stimulations, but bends upwards and at the peak of excitement orgasm also occurs and semen comes through the ventral orthotopic opening only. General physical examination was unremarkable, but external genitalial examination, shows, two external urethral meatus – one small pit like opening at the normal orthotopic position on the tip of glans penis and another on the dorsal surface of proximal penile shaft with epispadias and exposed urethral plate distal to this.. He had also dorsal chordee and ventral hooding with dorsal bifid glans penis. He had normally developed scrotum with normal both testes . Corpora cavernosa are developed but separated proximally. Spongiosa also developed and orthotopic anterior urethra can be palpated. Other systemic examinations revealed no abnormalities. Routine investigations like urine R/E, C/S, S.creatinine, blood sugar, CBC were normal. X-ray KUB revealed small separation of pubic symphysiis. USG of whole abdomen with KUB revealed significant PVR (77cc) with features of cystitis (sediments in bladder) with no other abnormality. RGU and MCU revealed duplicated urethra –with an accessory urethra arising from bladder neck, runs above the orthotopic one along the shaft terminating at the proximal part of dorsal penile shaft. The lower orthotopic urethra is normal with no stricture or abnormality except narrowing of the distal anterior urethra and external opening. Cystogram shows normal bladder with no VUR or divarticula except thickend wall. Urethrocystopic examination after dilatation of stenosed EUM of orthotopic (ventral) urethra showed normal anterior and posterior urethra containing sphincter and verumotanum and prostatic urethra opening into the bladder neck. Then cystoscope passed through the dorsal epispadiac urethra , which showed a less developed urethra, opening into the protruding bladder neck. Urinary bladder and ureteric orifices were normal . Then excision of accessory epispadiac urethra and the urethral plate done as high as possible near to bladder neck, followed by correction of chordee by ventral plication and repair of bifid corona glandis. He had an uneventful recovery ,though having a residual dorsal chordee, which was corrected by a second operation after 18 months, when excision of residual stump of accessory dorsal urethra followed by dermal graft repair of dorsal corporal body done. Bangladesh Journal of Urology, Vol. 21, No. 1, January 2018 p.48-51